On the System of Coupled Nondegenerate Kirchhoff Equations with Distributed Delay: Global Existence and Exponential Decay. (1st March 2021) - Choucha, Abdelbaki; Boulaaras, Salah Mahmoud; Ouchenane, Djamel; Alkhalaf, Salem; Mekawy, Ibrahim; Abdalla, Mohamed
Abstract : This paper studies the system of coupled nondegenerate viscoelastic Kirchhoff equations with a distributed delay. By using the energy method and Faedo-Galerkin method, we prove the global existence of solutions. Furthermore, we prove the exponential stability result.